Smartphone Use, Social Media, and Academic Procrastination in Secondary Education: A Multi Method Approach Investigation with Implications for School-Based Interventions - Abdullah, Haslee Sharil Lim; Amalia, Riza; Indreswari, Henny; Hambali, IM; Aditya, Ronal Surya; Rusnila, Rusnila (Buletin Konseling Inovatif, 2026)
Academic procrastination has become a significant challenge in digital learning environments, particularly among adolescents with high smartphone and social media usage. This study examines the relationship between mobile phone use and academic procrastination among 262 high school students in Indonesia using a cross-sectional survey, narrative review, and network analysis. Results show 75.6% of students exhibit medium and 20.2% high procrastination levels, with "alternative activities" like digital distractions as the main form (M = 15.87, SD = 2.92). No significant differences were found by gender (p = .067) or age (p = .412), but strong positive correlations emerged between gadget use (smartphone), social media, and procrastination (r ≈ 0.70), while family support correlated negatively (r ≈ –0.44). Network analysis identified protective factors such as family and school support, cultural values (gotong royong, pintar tuntang harati), and effective interventions including family counseling (d = 0.71), digital detox (d = 0.65), and school-based programs (d = 0.62), the effect sizes for these interventions were synthesized from the narrative review of existing literature and do not represent empirical findings from the current study. The findings underscore the need for culturally responsive, multi-tiered strategies that integrate self-regulation, digital wellness, and sociocultural support to reduce procrastination in technology-rich educational settings.